Causes of Dropout of Junior High School Students Under Khon Kaen Secondary Educational Service Area Office 25 - Tanachotipon, Parin; Narot, Pennee (Journal of Modern Learning Development, 2021)
This study investigated the following objectives: (1) To study the factors causing junior high school students in the Secondary Education Zone 25 of Khon Kaen Province to drop out of school; (2) To develop guidelines to prevent of junior high school students in the Secondary Education Zone 25 of Khon Kaen Province from dropping out of school; and (3) To propose guidelines to reduce or respond to the problem of drop-out of junior high school students. Data were collected by survey with the following groups of respondents: Homeroom teachers of junior high school students and school administrators, for a total of 81 participants. Individuals were selected by multi-stage sampling. The obtained data were analyzed by using Mean and Standard Deviation. A structured-interview questionnaire was used to collect data which allowed a 5-level estimation scale analysis. The quantitative data were analyzed by means and standard deviation. The qualitative data were processed using content analysis. The results are as follows: (1) The main cause of dropout occurred due to factors related to the students themselves, in addition to family, school and community factors; 2) Any attempt to prevent or resolve the problem of high school drop-out must be integrated, and involve cooperation among all sectors, whether from the national, community, school, and family levels. There needs to be mutual support among all sectors to address the problem.